Micropapillary Adenocarcinoma of the Lung that Metastasized to the Same Site in the Brain Twice: A Rare Case Report and Review of Literature - Faried, Ahmad; Agung, Rhonaz P.; Agustina, Hasrayati; Hernowo, Bethy S.; Arifin, Muhammad Z. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Adenocarcinoma (ADC) of the lung is the most common subtype of non-small cell lung cancer (NSCLC), occurring in ~40% of all patients with significantly higher incidence of brain metastasis compared with other subtypes of NSCLC. Among the five subtypes ADC of the lung, micropapillary predominant ADC may be more likely to metastasize. There are almost no reports of micropapillary ADC of the lung initially discovered to metastasis into the same site in the brain that has been previously operated. CASE REPORT: We reported a 54-year-old woman who was referred to ICU of Dr. Hasan Sadikin Hospital, Bandung, due to a decreased of consciousness. Head computed tomography scan revealed multiple isohypodense lesions in the right frontal with brain edema. She had craniotomy total tumor removal 8 months earlier and diagnosed as brain metastasis due to micropapillary ADC of the lung. She refused to receive chemoradiotherapy. At the operation site, multilobulated lesions were found, and hence, she was operated for the 2nd time at the same site with the first one, exhibited the same histology. Immunohistological shown positive results for thyroid transcription factor (TTF)-1 and cytokeratin (CK)-7; negative for CK-20, led to a diagnosis of micropapillary ADC of the lung. CONCLUSION: Herein, we reported our experience regarding a case of micropapillary ADC of the lung, considered as poorly differentiated ADC and associated with a high-grade lesion that metastasized to the same site that had been previously operated, twice. A definitive diagnosis was possible only through a histopathological examination along with a good communication between the surgeon and the pathologist.